Kejadian hipertensi pada lansia di Desa Mas Kecamatan Ubud Kabupaten Gianyar - Nila Pebriyan Suharto; Luh Seriani (E-Jurnal Medika Udayana, 2017)
Hypertension is a major public health problem in Indonesia and often occurs in the elderly. Hypertension often results in a dangerous state because its existence is often not recognized and frequently do not pose a significant complaints, until a complication occurs when the heart, brain, kidneys, eyes, blood vessels or other vital organs. Mas village is a village in Gianyar Bali Province that elderly hypertensive patients is still considered very high. In the 2014 annual report Ubud 1 health center, obtained 28.5% of all patients with hypertension in the working area of ??Ubud 1. Cross sectional descriptive study was using in this reasearch, and there were 42 elderly that choosen by consecutive method sampling. The reasearch data was coming from the blood pressure measurement and interview and was analyzed by quantitative descriptive. There were 92,9% of woman was suffered with hypertension, 76,2% was suffered with hypertension grade two, 42,9 % with excessive salt intake, 66,7% consuming of salty food, 9,5 % was smoking activities, 61,9% doing physical activities/sport and drinking cofee was 90,5%. Hypertension in elderly was tend occuring in some elderlu activities such as, excessive salt consumption, salty food, and drinking coffee. Keywords : hypertension, elderly, cross sectional, behavior, smoking